Identification of a gene cluster within the genome of Chilo iridescent virus encoding enzymes involved in viral DNA replication and processing - Müller, Ann-Kristin; Tidona, Christian; Darai, Gholamreza (Virus genes, 1999)
The nucleotide sequence of the genome of Chilo iridescent virus (CIV) between the genome coordinates 0.974 and 0.101 comprising 27,079 bp was determined. Computer-assisted analysis of the DNA sequence of this particular region of the CIV genome revealed the presence of 42 potential open reading frames (ORFs) with coding capacities for polypeptides ranging from 50 to 1,273 amino acid residues. The analysis of the amino acid sequences deduced from the individual ORFs resulted in the identification of 10 potential viral genes that show significant homology to functionally characterized proteins of other species. A cluster of five viral genes that encode enzymes involved in the viral DNA replication was identified including the DNA topoisomerase II (A039L, 1,132 amino acids (aa)), the DNA polymerase (ORF A031L, 1,273 aa), a helicase (ORF A027L, 530 aa), a nucleoside triphosphatase I (ORF A025L, 1,171 aa), and an exonuclease II (ORF A019L, 624 aa), all ORFs possessing the same genomic orientation. The DNA polymerase of CIV showed the highest homology (24.8% identity) to the DNA polymerase of lymphocystis disease virus lymphocystis disease virus 1 (LCDV-1), a member of the family Iridoviridae, indicating the close relatedness of the two viruses. In addition, four putative gene products were found to be significantly homologous to previously identified hypothetical proteins of CIV.
Gesehen am 19.03.2021